Servant leadership and thriving at work: perceived insider status and caring climate effects - Pratama , Marsianus Mahendra; Putranta, Martinus Parnawa (PHINISI, 2025)
This research aims to explore how servant leadership fosters thriving at work by testing the mediating role of perceived insider status and the moderating role of psychological climate for caring. Data were gathered with a cross-sectional survey. A total of 145 full-time employed respondents working in different industries involved in the research. The data analysed using Partial Least Squares Structural Equation Modelling Partial Least Squares (PLS-SEM). The findings reveal that servant leadership increases thriving at work both directly and indirectly via perceived insider status. In addition, psychological climate for caring climate is shown to strengthen the relationship between servant leadership and thriving, implying that supportive organizational environment enhances leadership effectiveness. This study contributes to the existing literature on positive organizational behavior by identifying perceived insider status as a key psychological mechanism and demonstrating that a caring climate serves as an important boundary condition shaping the servant leadership and thriving relationship.